Review on Major Factors Affecting the Successful Conception Rates on Biotechnological Application (AI) in Cattle (Global Journal of Medical Research, 2015)
Cows become fail to conceive with various factors including management failures, nutritional status, postpartum reproductive health, semen quality and other miscellaneous factor and hence reduce efficiency of AI service. Mainly heat detection skill by farmers and timing of insemination are the major factors that determine the success and failure of AI programme. Am/Pm rule is the way which helps to determine relative insemination times achieved in practice, since maximum fertility to artificial insemination occurs when cows are bred near the end of "standing heat". Ovulation occurs about 12 hours after the end of standing heat. Management limitations also synergize other factors like delivery problems which prone the AI service to have inefficient and poor result. Conservative stocking rate, a sensible year round feeding and herd health plan and adequate AI service are important to improve reproductive efficiency, and hence, economically benefit from the crossbreeding activities. Skill of inseminator is an important element in the success of the artificial insemination program and regular practice at inseminating time is required to maintain high conception rates. Besides to that site of semen deposition has an important role in achieving conception of AI in cattle. So that the deposition of semen in the uterine body resulting in higher non-return rate than cervical deposition. Cows are inseminated just into the short uterine body.
Keywords: heat detection; artificial insemination; inseminator; conception rate